Techno-economic Effect of R&D Outsourcing Strategy for Small and Medium-sized Enterprises: A Resource-Based Viewpoint - Huang, Y.; Lin, Chad; Lin, H. (Chinese Business Incubation Association, 2005)
The purpose of this research study is to investigate the techno-economic effects of an R&D outsourcing strategy for small and medium-sized enterprises (SMEs). Based on a resource-based viewpoint, the techno-economic effects of an R&D outsourcing strategy are found to be dependent on the level of product innovation and of previous R&D outsourcing experience. The empirical results demonstrate that R&D outsourcing can enhance technological capabilities when applied to product developed under radical product innovation, and for SMEs with a rich experience in R&D outsourcing, their R&D outsourcing practice can help to generate financial profits via this type of products. Research and managerial implications are also discussed here.